Renewal of Islamic Jurisprudent Terminology by Sheikh Mustafa Alzarq - Alajmi, محمد مهدي محمد (Dirasat: Shari'a and Law Sciences, 2022)
Objectives: This research aims to trace the terminologies proposed by Sheikh MUSTAFA ALZARQA in his innovative project (Islamic jurisprudence in its new model) along with studying these terminologies in terms of its attribution and the grounds of its coinage. In this regard, the research aims to urge the contemporary islamic jurists to renew the jurisprudent terminology whenever needed. Methods: In this research, the descriptive analytical approach was used, by introducing the term with clarifying its form and the context in which it is presented, presenting the summary of the term, and studying the term in terms of its attribution and its coinage grounds. Results: Sheikh Mustafa Alzarqa’s interest in renewing Islamic jurisprudential terms stemmed from his thoughtful linguistic mind, and the most important documents on which he relied: coinage in determining the word with some of its indications, Islamic Law text, the meaning of Arabic vocabulary, and the rules of morphology and derivation. The important reasons that led Sheikh to coin these terms are: the distinction in the naming based on the distinction of concepts and their different effects, preventing verbal ambiguity due to the same writing, and keeping pace with the modern language. Conclusions: Due to its importance, the research concluded with a recommendation to study the Islamic jurisprudential definitions coined by Sheikh MUSTAFA ALZARQA, such as his definition of ownership, money, right, etc..